Mencari Kepastian Hukum dan Keadilan: Dilema Penahanan dalam Proses Pidana - Firmansyah Firmansyah (CV. ITTC INDONESIA, 2026)
Detention is one form of coercive measure given by law-to-law enforcement officers to ensure the smooth running of the criminal justice process. On one hand, detention is necessary to make sure that suspects or defendants do not flee, destroy evidence, or repeat the criminal act. However, on the other hand, detention can also potentially restrict human rights, especially the right to freedom and the presumption of innocence. This situation creates a dilemma between the need for legal certainty and the demand to achieve justice. This article aims to analyze the implementation of detention in the criminal process in Indonesia and examine how a balance between legal certainty and justice can be achieved. This study uses a normative legal research method with a legislative approach and a conceptual approach. Research results show that even though the detention regulations in the Criminal Procedure Code (KUHAP) provide a clear legal basis, the practice of detention still faces various issues, such as the tendency for excessive use of detention and the suboptimal mechanism for supervising law enforcement officials' actions. Therefore, applying the principle of proportionality and respecting human rights is necessary so that the goals of law enforcement can be achieved without disregarding the values of justice.